Relationship Between Body Image and Self-Confidence of Students - Melina, Rahel; Ardianti, Tanti; Erwinda, Lira; Sagita, Dony Darma; Kasman, Apri (Asosiasi Asesmen Pendidikan (AAP), 2025)
Adolescents face various developmental challenges, ranging from academic demands, social relationships, to the search for identity, all of which can affect how they assess themselves. This study aims to determine the effect of body image on students' self-confidence and its implications for guidance and counseling services. The research design used a quantitative correlational approach. The study sample consisted of 138 grade 10 students selected using a stratified random sampling method. The instruments used were the Body Image Inventory and the self-confidence Inventory. Data analysis was carried out using simple regression techniques and correlational analysis. The results showed that body image significantly influenced students' self-confidence. In addition, it was found that adolescents' self-confidence was in the moderate category, body image was in the neutral category, and both had a significant positive relationship.